Guy Mundlak. Organizing Matters. Two Logics of Trade Union Representation. ILERA Publication Series, International Labour Organization, 2020. 265 pp. - Gotelli, Agustín (2022)
En el libro Organizing Matters. Two Logics of Trade Union Representation (La organización importa. Dos lógicas de representación sindical) publicado por la Organización Internacional del Trabajo, Guy Mundlak, indaga en las estrategias de revitalización sindical de sindicatos de cuatro paises, en el marco del debilitamiento de los sistemas corporativos de representación laboral.
In the book Organizing Matters. Two Logics of Trade Union Representation (The organization matters. Two logics of union representation) published by the International Labor Organization, Guy Mundlak, investigates the union revitalization strategies of unions in four countries, in the framework of the weakening of corporate systems labor representation.
No livro Organizing Matters. Two Logics of Trade Union Representation (A organização importa. Duas lógicas de representação sindical) publicada pela Organização Internacional do Trabalho, Guy Mundlak, investiga as estratégias de revitalização sindical dos sindicatos em quatro países, no quadro do enfraquecimento dos sistemas corporativos de representação trabalhista.
Keywords: Sindicatos; Afiliación; Organización; Acción colectiva; Unions; Affiliation; Organization; Collective action; Sindicatos^lpt; Filiação; Organização; Ação coletiva